DESIGN AND SIMULATION OF INTRACAVITY FORWARDS AND BACKWARDS OPTICAL PARAMETRIC OSCILLATORS - Kneller, Joshua (My University, 2024)
Intracavity optical parametric oscillators are an attractive method for generating light throughout the infrared (IR) wavelength range due to their ability to simultaneously achieve high output powers and narrow linewidths. Despite the extensive volume of literature published on this type of laser, there are gaps in existing models that must be addressed to aid in the development of these lasers. A new model for an intracavity backwards optical parametric oscillator (IC-BOPO) is proposed to determine the feasibility of using periodically poled lithium niobate (PPLN) as a nonlinear material in a continuous wave IC-BOPO. It is shown that it is possible to reach the laser threshold when using a low power laser diode as the pump source and a commercially available off-the-shelf PPLN. It is also shown that the proposed laser is capable of achieving watt level output power with picometer linewidth at mid-infrared wavelength using a 20 W pump laser diode. To further optimize the lasers, a systematic study is presented which investigates the effects of multiple parameters on the laser performance such as nonlinear crystal length, cavity size, output coupler radius and pump laser spot size. Additionally, effects such as thermal lensing and beam overlap within the nonlinear crystal are considered. With proper cavity setup, it is possible to reach the laser threshold with PPLN crystal as short as 2 cm with a 10 W pump laser diode. A new model for a passively Q-switched intracavity optical parametric oscillator (IC-OPO) is also presented. The effects of thermalization, excited state absorption in the Q-switch crystal, beam overlap in the nonlinear crystal and nonlinear loss due to pump depletion in the nonlinear crystal are all considered. The model accurately calculates both the temporal and output power characteristics of the laser. The calculated signal pulse width from the model was 1.75 ns compared to the experimentally measured value of 2 ns.
Keywords: Nonlinear Optics; Laser